Training and Competition Load Monitoring and Analysis of Women's Amateur Basketball by Playing Position: Approach Study - Reina Román, María; García-Rubio, Javier; Feu, Sebastián; Ibáñez, Sergio José (Frontiers in Psychology, 2019)
Currently, the number of women involved in sport is increasing. Although, research on their characteristics and performance is scarce. A great amount of research on men's basketball is available, but it is unknown if it can be applied to women's basketball. The objective of this research was to characterize the internal and external load performed by female basketball players during training and sports competition according to playing positions through inertial devices. The participants in the following study were 10 amateur basketball players who competed at regional level (21.7±3.65 years; 59.5±12.27 kg and 168.5±3.56). Data were collected in games of the final phase (n=8) and from 5 vs. 5 training tasks (n=47). All the analyses were run according to playing positions. Each player was equipped with a GarminTM Heart Rate Band and WimuTM inertial device that monitored physical activity and movement in real time. The results obtained showed that the load experienced during competition was significantly higher (p<.001) than during training (Heart Rate, Player Load, Steps, Jumps and Impacts). There were also differences according to playing positions, mainly between the backcourt and frontcourt players (p<.001). The players must work in higher areas of heart rate during training, mainly in Z4 and Z5, increasing their HRmáx y HRavg. The training doesn’t equal the load supported and the distance performe in competition, so it is necessary to pay more attention during training. This information allows us to develop adequate training protocols adjusted to the specific individual requirements of the sports competition.